The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1007/s11837-021-05080-4
|View full text |Cite
|
Sign up to set email alerts
|

On the Influence of AlSi10Mg Powder Recycling Behavior in the LPBF Process and Consequences for Mechanical Properties

Abstract: By using additive manufacturing techniques like the laser powder bed fusion (LPBF) process, parts can be manufactured with high material efficiency because unfused powder material can be reconditioned and reused in consecutive manufacturing jobs. Nevertheless, process by-products like spatters may influence the powder quality and hence alter the mechanical properties/performance of parts. In order to investigate these dependencies, a methodology and a standard build job for the recycling behavior of the lightw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In order to make the PBF‐LB/M process energy and economically sustainable, the recycling of powders becomes necessary. A strong relationship between powder recycling and the quality of the final part has been reported in the literature 22,23 . As extensively demonstrated by Wang et al, the effects of reuse are highly dependent on the type of alloy 24 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In order to make the PBF‐LB/M process energy and economically sustainable, the recycling of powders becomes necessary. A strong relationship between powder recycling and the quality of the final part has been reported in the literature 22,23 . As extensively demonstrated by Wang et al, the effects of reuse are highly dependent on the type of alloy 24 .…”
Section: Discussionmentioning
confidence: 80%
“…A strong relationship between powder recycling and the quality of the final part has been reported in the literature. 22,23 As extensively demonstrated by Wang et al, the effects of reuse are highly dependent on the type of alloy. 24 In particular, aluminium is a strongly electronegative metal and its strong oxygen affinity explains the importance of monitoring the use of Al-based alloys in the PBF-LB/M process.…”
Section: Discussionmentioning
confidence: 93%
“…When setting up the experimental plan, it was assumed that the embedded oxides might help improve the high-temperature characteristics, as the respective performance of ceramic particle-reinforced Al-based metal matrix composites (MMCs) suggests. This notion is partially supported by Weiss et al, who showed that improvement in room temperature yield and ultimate tensile strength can indeed be observed in specimens based on recycled powders [ 24 ]. To verify this assumption, oxygen content was determined on printed samples using a trace element analyzer of type ONH2000 supplied by Eltra GmbH, Haan, Germany.…”
Section: Methodsmentioning
confidence: 78%
“…The study by Weiss et al also considered Al, Si, Mg and hydrogen content, showing significant variation in the case of oxygen only. Within this somewhat higher range of oxygen content, Weiss et al found no significant influence on density of LPBF samples and only a slight increase in Vickers hardness, with the latter exhibiting strong scatter [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation